2015
DOI: 10.21863/ijhts/2015.8.2.011
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Factors Influencing Residents Perception of the Impacts of Tourism in Goa

Abstract: To strategically utilize resources to minimize the negative impacts of tourism and increasing the social support for tourism development, the present study examined the residents of the State of Goa by using the model developed by Perdue et al. (1990), later extended by Mc Gehee, et al. (2002), and also based on social exchange theory, tried to determine whether personal characteristics and personal benefits from tourism influence perception of tourism as well as support for tourism development, and what facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Personal benefits relate to the benefits of resources, environmental protection, participation in decision making in tourism. Mello et al, (2015) found that the benefits of a person had a significant positive effect on the perception of the positive impact of tourism.…”
Section: Methodsmentioning
confidence: 99%
“…Personal benefits relate to the benefits of resources, environmental protection, participation in decision making in tourism. Mello et al, (2015) found that the benefits of a person had a significant positive effect on the perception of the positive impact of tourism.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, Haley, Snaith and Miller () argued that neither age nor sex have any bearing on the attitudes toward tourism. D'Mello et al (), Rasoolimanesh, Jaafar, Kock, and Ramayah (), and Látkova and Vogt (), as well as Tovar and Lockwood (), also studied the extent to which age or educational level influence the perception about tourism. As for ethnicity, Andereck et al () came to the conclusion that Hispanic individuals have a more positive view about the effects of tourism than those of Anglo‐Saxon origin.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the factors influencing residents’ perception about tourism have been extensively investigated, it becomes necessary to replicate studies in various locations and at different points in time (D'Mello et al, ). Furthermore, a large number of these works have focused on North America and, to a much lesser extent, on other world regions such as Australia, New Zealand, or the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…SET has been advocated as the most appropriate framework for explaining residents' perceptions on the impact of gambling tourism (Giacopassi and Stitt 1994;Pizam and Pokela 1985;Stitt et al 2003); which suggests that residents would evaluate benefits and costs associated with a tourism avenue and then decide whether they should support it or not, i.e., in other words residents becomes supporters if their quality of life is improved, opposers if their quality of life is hampered, or become neutral if no change takes place. The more the benefits, the more residents will become supportive and vice versa, depending on their demographic characteristics (D'Mello et al 2015(D'Mello et al , 2016aKamat et al 2016). Film induced tourism, like other forms of tourism, introduced both positive and negative impacts on a destination (Heitmann 2010).…”
Section: Residents Perception About Film Tourism and Quality Of Lifementioning
confidence: 99%
“…In 2004, the then government Bharatiya Janatha Party (BJP) at the centre and also in Goa unanimously decided to make Goa the permanent venue for IFFI and inaugurated the 35th International Film Festival of India (IFFI-2004) in Panaji, Goa on November 29, 2004. This initiative was based on the unique blend of Indo-Portuguese culture, cuisine and lifestyle but most importantly, Goa's unique selling proposition (USP), her friendly, warm hearted and hospitable people (D'Mello et al 2015). Historically ancient Goa was self-ruled by Gaonkaris (1000 BC-500 BC), Hindu Dynasties (500 BC-1330 AD), Islamic dynasties (1326-1510), Portuguese (1510Portuguese ( -1961, until it became liberated in 1961 (Wiki 2015a, b).…”
Section: Introductionmentioning
confidence: 99%